Modeling the evolution of the parent body of acapulcoites and lodranites: a case study for partially differentiated asteroids - Neumann, Wladimir; Henke, Stephan-Markus; Gail, Hans-Peter; Schwarz, Winfried H.; Trieloff, Mario; Hopp, Jens (Icarus, 2018)
The acapulcoites and lodranites are rare groups of primitive achondrites that originate from a common parent body and are of particular interest since they experienced only partial melting. We calculated thermal evolution and differentiation models of the parent body of the Acapulco-Lodran meteorite clan. The models were compared to the maximum metamorphic temperatures, differentiation degree, and thermo-chronological data available. An optimized set of parameters which fits to the data was determined: A radius of≈260km, a formation time of≈1.7 Ma after CAIs and an initial temperature of≈250K. The burial depths derived are 7-13km. The respective layers experienced minor melting and small-scale melt migration, matching the differentiation degree of the meteorites. The resulting structure has an iron core, a silicate mantle, a partially differentiated layer, and an undifferentiated outer shell. Our results indicate a larger size, an earlier formation time, and a formation closer to the sun of the parent body of acapulcoites and lodranites than typical estimates for ordinary chondritic parent bodies, consistent with a stronger thermal metamorphism. The burial depths support excavation by a single impact. The presence of core and mantle indicates that these meteorites could share a common parent body with differentiated stony and iron meteorites.
Gesehen am 29.08.2019